(untitled) (Pedagogy of Higher and Secondary Education, 2006)
The role and importance of the didactic game in the system personality-orientated studying are considered in this article. It has been shown, that successful employment of the games influence on improvement of the quality knowledge, skills and habits of the pupils, stimulate their creative work, initiative, independence and activity.